Superimposed folding and thrusting by two phases of mutually orthogonal or oblique shortening in analogue models. (February 2016) - Deng, Hongling; Koyi, Hemin A.; Nilfouroushan, Faramarz
Abstract: Orogens may suffer more than one phase shortening resulting in superposition of structures of different generations. Superimposition of orthogonal or oblique shortening is studied using sandbox and centrifuge modelling. Results of sand models show that in orthogonal superimposition, the two resulting structural trends are approximately orthogonal to each other. In oblique superimposition, structures trend obliquely to each other in the relatively thin areas of the model (foreland), and mutually orthogonal in areas where the model is thickened during the first phase of shortening (i.e. the hinterland). Thrusts formed during the first shortening phase may be reactivated during the later shortening phase. Spacing of the later phase structures is not as wide as expected, considering they across the pre-existing thickened wedge. Superposition of structures results in formation of type 1 fold interference pattern. Bedding is curved outwards both in the dome and basin structures. Folded layers are dipping and plunging outwards in a dome, while they are dipping and plunging inwards in a basin. In the areas between two adjacent domes or basins (i.e. where an anticline is superimposed by a syncline or a syncline is superimposed by an anticline), bedding is curved inwards, and the anticlines plunge inwards and the synclines outwards. The latter feature could be helpful to determine the age relationship for type 2 fold interference pattern. In tectonic regions where multiple phases of shortening have occurred, the orogenic-scale dome-and-basin and arrowhead-shaped interference patterns are commonly formed, as in the models. However, in some areas, the fold interference pattern might be modified by a later phase of thrusting. Similar to models results, superimposition of two and/or even more deformation phases may not be recorded by structures all over the tectonic area. Highlights: This Ms focuses on superimposition of structures formed during two phases of mutually orthogonal or oblique shortening using results of analogue models and three natural examples. Superimposition of folding and thrusting and fold interference patterns are discussed in this study. Signatures of superimposed structures vary from different parts of the shortened area and across an erosional level. Trend of later structures is influenced by the mode of superimposition, i.e. orthogonal or oblique. Propagation and spacing of later thrusts are influenced by lateral thickness change caused by an early-phase of shortening.